1998
DOI: 10.1557/jmr.1998.0079
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of microstructures produced by creep of Ti–48Al–2Cr–2Nb–1B: Thermal and athermal mechanisms

Abstract: A g-based TiAl alloy with equiaxed microstructure and fine grain size has been studied to analyze the deformation mechanisms responsible for the creep behavior. The microstructures produced by creep and high temperature deformation have been examined by TEM to obtain information about the different aspects characterizing the primary and secondary stages of creep. Mechanical twinning has been confirmed to occur in a fraction of the grains that never exceeds 50% while 1͞2 ͗110͘ dislocations are active within all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…pct), which exhibits a steady-state creep regime of about 3 pct strain or more when tested at 700 ЊC to dislocation glide, i.e., power-law breakdown. It is clear from Figure 11 that the creep resistance of the PS-DP matefor stresses ranging between 260 and 360 MPa; [27] this finding was found for both the equiaxed and lamellar rial resembles that of NL material, both of which are superior to the creep behavior of the DP material. The improved microstructures.…”
Section: Creep Propertiesmentioning
confidence: 81%
“…pct), which exhibits a steady-state creep regime of about 3 pct strain or more when tested at 700 ЊC to dislocation glide, i.e., power-law breakdown. It is clear from Figure 11 that the creep resistance of the PS-DP matefor stresses ranging between 260 and 360 MPa; [27] this finding was found for both the equiaxed and lamellar rial resembles that of NL material, both of which are superior to the creep behavior of the DP material. The improved microstructures.…”
Section: Creep Propertiesmentioning
confidence: 81%
“…Later, Appel et al (1999) presented the idea that twins would constitute a major source of hardening because the twin/matrix interface or twin intersection may serve as barriers for dislocation glide. On the other hand, Seo et al (1997) and Morris and Lipe (1997); Morris and Leboeuf (1998) argued that twin interfaces hinder dislocation motion and, therefore, harden the γ-phase. This was further followed in a detailed study (Skrotzki, 2000) where Skrotzki suggested that coherent twin boundaries seems to represent only a minor obstacle to dislocation slip, since they can pass the interface by suitable dissociation processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that twinning plays a more active role in microstructure evolution than in strain contribution. While it has been proposed [30][31][32][33][34][35] that the formation of twin interfaces refines the microstructure and thus causes hardening, the coincident occurrence of the minimum creep rate and twinning leads us to believe that it is probably a flow softening process. Internal and compatibility stresses set up at lamellar and grain boundaries are probably relieved by twinning.…”
Section: Microstructural Stability and Tertiary Creepmentioning
confidence: 99%